CONFIRMATION OF THE IRRATIONALITY OF THE EULER CONSTANT (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
I prove that the Euler constant is irrational by showing that it cannot be written as a quotient of two integers. In fact, going from the rational form